2018
DOI: 10.24815/ijolta.v1i3.10712
|View full text |Cite
|
Sign up to set email alerts
|

Grammar and vocabulary testing scores in L2 reading

Abstract: In language testing bibliography, it has been suggested that L2 grammar and vocabulary scores strongly and positively correlate with L2 reading comprehension. Jeon and Yamashita (2014), conducting a large-scale meta-analysis study, found strong correlations among these two variables: r=.85 for grammar and r=.79 for vocabulary in different tasks. Following this paradigm, the current study examines this relationship (performance on reading skills and language use – grammar and vocabulary) integrated into a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…In line with this, grammar knowledge is one of the factors in reading comprehension (Azizah et al, 2017). Some previous researchers found that grammar knowledge and reading interest together with reading comprehension positively correlate (Alek & Handayani, 2018;Amir & Shahi, 2016;Mouti & Ypsilandis, 2018). It is implied that reading interest and grammar knowledge affects reading comprehension.…”
Section: The Relationship Between Grammar Knowledge and Reading Compr...mentioning
confidence: 79%
See 1 more Smart Citation
“…In line with this, grammar knowledge is one of the factors in reading comprehension (Azizah et al, 2017). Some previous researchers found that grammar knowledge and reading interest together with reading comprehension positively correlate (Alek & Handayani, 2018;Amir & Shahi, 2016;Mouti & Ypsilandis, 2018). It is implied that reading interest and grammar knowledge affects reading comprehension.…”
Section: The Relationship Between Grammar Knowledge and Reading Compr...mentioning
confidence: 79%
“…Then, grammar is necessary for reading comprehension based on previous research. Mouti & Ypsilandis (2018) conducted a study about grammar and vocabulary to reading. The finding showed that grammar has high contribution to reading.…”
Section: Introductionmentioning
confidence: 99%